Caracterização química da própolis produzida no Sul do Brasil - Machado, Christiane Schineider (2018)
The main objective of this work was the development of qualitative and quantitative analytical methodologies for the chemical investigation of propolis from the State of Paraná by chromatographic techniques (HPLC-DAD and GC-MS). Overall, 44 samples of propolis from Paraná were analyzed and their levels of bioactive compounds were compared with green propolis from São Paulo and Minas Gerais, brown propolis from Santa Catarina and red propolis from Bahia. Figures of merit of the HPLC-DAD methodology were investigated: linearity R2 > 99% and no evidence of lack-of-fit (p > 0.01); recoveries between 84.30-119.52% (only 3,4-di-O-Caffeoylquinic acid recovery rate was higher, 138.77%); precision up to 11.76% (repeatability) and 14.56% (intermediate precision); detection and quantification limits (LODs and LOQs) of 0.74-3.02 μg/mL and 2.48-10.07 μg/mL. It was found that p-coumaric and 4-hydroxy-3,5-diprenylcinnamic acids and kaempferide were widely spread in Brazilian propolis. Also, high levels of 3,5-di-caffeoylquinic and 3,4-di-O-caffeoylquinic acids were found in most propolis from Paraná and in green propolis. 4-O-caffeoylquinic acid was abundant in most propolis from Paraná but not in propolis from Minas Gerais, Santa Catarina and Bahia. It was also possible to calculate the total content of classes of bioactive compounds, such as caffeoylquinic and benzoic acids, phenylpropanoids such as p-coumaric acid derivatives, flavonols and dihydroflavonols. The antimicrobial activity prospection of the extracts indicated that most propolis presented high antimicrobial activity. MIC values for the Gram-positive bacteria E. faecalis were poorly correlated with the total amount of p-coumaric acid derivatives (r = -0,3175, p = 0,0448) and flavonols (r = - 0,3291, p = 0,0312) in extracts, while the MIC values for the Gram-negative strain P. aeruginosa were also poorly correlated to the levels of flavonols (r = - 0,4815, p = 0,0011) and dihydroflavonols (r = - 0,3548, p = 0,0195). Principal Component Analysis was performed in order to classify the propolis samples from Paraná according to their levels of bioactive compounds and biological activity. Afterward, linear discriminant functions that allowed to discriminate propolis samples due to their geographical origin were calculated. In this way, the levels of bioactive compounds and biological activities of propolis extracts can be related to the brown propolis produce in specific regions of Paraná. This relationship may be useful to confirm the geographical origin of commercial samples of propolis. Finally, GC-MS analysis allowed the confirmation of benzoic acid, 3-hydroxy-4-methoxybenzaldehyde, cinnamic acid, p-coumaric acid, hexadecanoic acid, oleic acid, isopimaric acid, dehydroabietic acid, abietic acid, octacosane and β-amyrin in extracts of propolis.